Eco-friendly optical sensor membrane for nickel ion detection in water and food samples - Abdullah H. Alluhayb; Alaa M. Younis; Ahmad O. Babalghith; Alaa S. Amin (Results in Chemistry)
A sustainable method is investigated for the accurate, selective, and highly sensitive identification of minimal nickel ion concentrations across various environments. A unique optical sensing membrane is proposed for detecting Ni2+ ions, utilizing the entrapment of 5-(2-benzothiazolylazo)-8-hydroxy-quinoline (BTAHQ) within a matrix of polyvinyl chloride (PVC) combined with dioctyl adipate (DOA). The sensor exhibits a broad linear span ranging from 2.5 to 110 ng mL−1 under pH 4.0 conditions, featuring quantification and detection limits of 2.47 and 0.75 ng mL−1, respectively. The sensor’s maximum wavelength is recorded at 659 nm. Remarkably, the sensor membrane exhibits complete reversibility in its operation, showcasing superior specificity for Ni2+ ions even in the presence of a wide range of competing cations and anions within the solution. The membrane exhibited excellent durability for 3.0 min, featured a swift response time (5.0 min), and demonstrated no detectable signs of reagent leaching. The sensor response exhibited a low coefficient of variation (CV) of 1.47 % for 60 ng mL−1 of Ni2+ ions, and the CV among seven sensor membranes was 1.63 %. Regenerating the sensor is a straightforward process accomplished with 0.5 mL of 0.1 M HNO3 solution for 3.0 min. Its full reversibility and excellent selectivity for Ni2+ ions in thiel buffer contribute to its efficacy. The suggested optical sensor was effectively employed for nickel determination in food and water samples.